Studi Awal Pengembangan Tumbuhan Obat-Obatan Sebagai Destinasi Wisata Kesehatan Berbasis Biodiversitas Di Desa Karang Sidemen, Nusa Tenggara Barat - Hayati; valentino, niechi; Setiawan, Budhy; Webliana, Kornelia; Prasetyo, Andrie Ridzki; Gozali, M. Rijalul; Hadi , Muhammad Anwar; Syahruanda, Eggi (Universitas Mataram, 2024)
Karang Sidemen Village plays an important role in protecting and preserving the rich biodiversity around the Mount Rinjani area, especially in the use of medicinal plants as an inseparable part of the